POSSIBILITIES OF MODERN TECHNOLOGIES OF VISUALIZATION AND MODELING IN ORTHOPEDICS AND THEIR ROLE IN DEVELOPMENT OF INDIVIDUAL CONSTRUCTIONS IN HIP ARTHROPLASTY - A. N. Kovalenko; I. I. Shubnyakov; S. S. Bilyk; A. O. Denisov; R. M. Tikhilov (Вестник хирургии имени И.И. Грекова)
The article presents the authors’ experience. Medical visualization is applied in orthopedics on all stages such as diagnostics, treatment planning and control of the results. Modern approaches in instrumental diagnostics and specialized application-dependent software allowed a new qualitative level of orthopedics and medical care in different areas of medicine. Modern technologies gave a lot of opportunities to doctors in order to improve diagnostics at higher level, make an individual planning of operations and built individual implants, when it wasn’t possible to use standard constructions.